Examining Perceptions of Computerized Physician Order Entry in a Neonatal Intensive Care Unit - Beam, Kristyn S.; Cardoso, Megan; Sweeney, Megan; Binney, Geoff; Weingart, Saul N. (Applied Clinical Informatics, 2017)
Background: Computerized provider order entry (CPOE) is a technology with potential to transform care delivery. While CPOE systems have been studied in adult populations, less is known about the implementation of CPOE in the neonatal intensive care unit (NICU) and perceptions of nurses and physicians using the system.Objective: To examine perceptions of clinicians before and after CPOE implementation in the NICU of a pediatric hospital.Methods: A cross-sectional survey of clinicians working in a Level III NICU was conducted. The survey was distributed before and after CPOE implementation. Participants were asked about their perception of CPOE on patient care delivery, implementation of the system, and effect on job satisfaction. A qualitative section inquired about additional concerns surrounding implementation. Responses were tabulated and analyzed using the Chi-square test.Results: The survey was distributed to 158 clinicians with a 47% response rate for pre-implementation and 45% for post-implementation. Clinicians understood why CPOE was implemented, but felt there was incomplete technical training. The expectation for increased job satisfaction and ability to recruit high-quality staff was high. However, there was concern about the ability to deliver appropriate treatments before and after implementation. Physicians were more optimistic about CPOE implementation than nurses who remained concerned that workflow may be altered.Conclusions: Introducing CPOE is a potentially risky endeavor and must be done carefully to mitigate harm. Although high expectations of the system can be met, it is important to attend to differing expectations among clinicians with varied levels of comfort with technology. Interdisciplinary collaboration is critical in planning a functioning CPOE to ensure that efficient workflow is maintained and appropriate supports for individuals with a lower degree of technical literacy is available.Citation: Beam KS, Cardoso M, Sweeney M, Binney G, Weingart SN. Examining perceptions of computerized physician order entry in a neonatal intensive care unit. Appl Clin Inform 2017; 8: 337–347 https://doi.org/10.4338/ACI-2016-09-RA-0153
Keywords: Implementation and deployment; electronic health records and systems; clinical decision support; inpatient; inpatient CPOE; neonatology